Problems and Dilemmas: ASEAN Commitments in Disaster Management - Arumbinang, Mohammad Hazyar (Universitas Muhammadiyah Yogyakarta, 2021)
This research aims to elaborate the problems and dilemmas of disaster management and emergency response of ASEAN. This paper has adopted normative qualitative legal research with statutory approaches. The data will be analysed by using descriptive-analytical analysis. The research found that there are some major problems that faced by ASEAN members in working collectively on the disaster management and emergency response, such as non-intervention principles and sovereignty principles. The Southeast Asian region is remarkably vulnerable to natural and man-made disasters which repeatedly cause devastations to both human lives and properties. The experience has shown that local government and holders with their capacity have proved their ability to handle small and medium scale emergency response, but for some circumstance the host state sometimes cannot deal with this issue. Due to that issue Association of Southeast Asian Nations (ASEAN) as the regional organization in Southeast Asia playing an importance role to building a well-prepared disaster management through join collaboration among ASEAN member by reason of humanity.